Trustworthy AI African Perspectives - Eke, Damian Okaibedi; Wakunuma, Kutoma; Akintoye, Simisola; Ogoh, George; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This book is an Open Access Publication. The Guidelines for Trustworthy AI developed by the European Commission High-Level Expert Group on AI is a framework that has been developed to promote and achieve the trustworthiness of AI systems. It provides seven ethical principles that can be operationalised in socio-technical systems to realise responsible AI design and deployment. The content of this book is shaped around these principles. In chapter one, the concept of Human Agency and oversight will be described from the lens of a social-cultural understanding of Agency, Autonomy, and oversight including a debate on the place of human rights and power dynamics. Beyond the Trustworthy AI discourse, this book will appeal to the wider AI developers community, civil society, policymakers, ICT and the RRI community. It will also appeal to other subject areas within the Social Sciences and Humanities including; Law and Technology and Digital Culture. Damian Okaibedi Eke is Assistant Professor at the School of Computer Science, University of Nottingham, UK. Kutoma Wakunuma is Associate Professor in Information Systems at De Montfort University where she works within the Centre for Computing and Social Responsibility (CCSR). Simisola Akintoye is an Associate Professor of Law at Northumbria University School of Law. She is interested in multidisciplinary research around legal and ethical regulation of Emerging Technologies and Corporate Sustainability. George Ogoh is a Senior Research Fellow in the School of Computer Science, University of Nottingham.
Chapter 1 African Perspectives of Trustworthy AI: An introduction -- Chapter 2 Prefiguring Afro-centric and inclusive AI digital commons: A normative African perspective to AI development, deployment, and governance -- Chapter 3 Building Trustworthiness as a requirement for AI in Africa: Challenges, Stakeholders and Perspectives -- Chapter 4 Trust me, I am an Intelligent and Autonomous System: Trustworthy AI in Africa as Distributed Concern -- Chapter 5 Afrocentric Trustworthy Framework for Improved Artificial Intelligence Powered Health Management Tool for Africans -- Chapter 6 Resource Allocation for Trustworthy Artificial Intelligence Projects in Africa -- Chapter 7 Context-Aware Africa-led Designing of Responsible Artificial intelligence Technologies -- Chapter 8 Exploring Trustworthy AI in Nigeria: A Focus on Safety in Road Traffic -- Chapter 9 Trustworthy AI in Healthcare: exploring ethics in Digital Health Technologies in Nigeria -- Chapter 10 Artificial Intelligence (AI) Onto-norms and Gender Equality: Unveiling the Invisible Gender Norms in AI Ecosystems in the Context of Africa -- Chapter 11 Relationality and Data Justice for Trustworthy AI Practices in Africa -- Chapter 12 Decoloniality as an essential Trustworthy AI requirement -- Epilogue.
Keywords: Science -- Social aspects; Artificial intelligence; Human geography; Science and Technology Studies; Artificial Intelligence; Human Geography